Business Recovery and Continuity in a Mega Disaster : cybersecurity lessons learned from the COVID-19 pandemic - Das, Ravindra (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis Group, LLC, 2022)
"The COVID-19 Pandemic has changed the entire world to levels that were not even thought of before. This publication is intended to be a how-to book to fully prepare CIOs and CISOs for the next disaster to happen, whether natural or manmade, with the various lessons that have been learned thus far from COVID-19"--
Includes bibliographical references and index.
Keywords: Emergency management; Computer security; COVID-19 Pandemic, 2020- -- Economic aspects